NEW MEDIA AND INTERNATIONALIZATION OF UNIVERSITIES: REPRESENTATION OF INTERNATIONALIZATION ON THE UNS WEBSITE JUNE-AUGUST 2018 - Likha Sari Anggraeni; Indriana Mega Kresna; Monika Sri Yuliarti; Ismi Dwi Astuti Nuraheni (Jurnal Ilmu Komunikasi, 2020)
With regard to globalization, the field of education is undergoing a system regeneration that enables the exchange of information, the development of organizational culture and the development of education systems with an international dimension. Internationalization becomes a system which is then widely applied to educational institutions such as universities. The internationalization process carried out by a tertiary institution can be reviewed through the ranking of educational institutions carried out by various world ranking institutions such as QS Stars and can also be monitored through an information platform owned by the relevant agency. Internationalization of tertiary institutions has begun to be implemented in Indonesia and is a program being promoted by the Ministry of Research and Higher Education. Universitas Sebelas Maret (UNS) is one of the tertiary institutions that is working towards internationalization. Since the last few years, UNS has continued to carry out programs related to internationalization. In addition, UNS also seeks to communicate the internationalization program that is being undertaken to the public by publishing a campus agenda through an information platform such as a website. This study looks at the representation of the UNS website in conveying information to the public and its stakeholders based on international indicators of QS Star ranking. The data used is in the period June August 2018. The results of the study show that only academic reputation and international student ratios are the most widely displayed on the UNS website.